Aesthetic Value in Marketing Art Gallery: Conceptualization and Scale Development - Subiharto, Joko; Dharmmesta, Basu Swastha; Sutikno, Bayu; Siswomihardjo, Sari Winahjoe (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2024)
This study aims to develop a measurement tool for a new concept in aesthetic marketing called Aesthetic Value. The paper provides a framework for understanding individual motivations in consuming art galleries, starting with exploring art theory, aesthetics, and experience as a source of aesthetic value. The research then defines the construct and its dimensions, which are used to create a measurement tool and develop a conceptual model. Data collected from survey is used to evaluate the overall aesthetic value model. Finally, Exploratory Factor Analysis (EFA) determines the number of components that should be retained in the construct. The study concludes that Aesthetic Value has four dimensions: artwork, facilities-place, knowledge, and emotion. This conceptualization provides a robust foundation for understanding customer value in the context of consuming art galleries by considering various relevant elements of Aesthetic Value. The article also discusses the potential use of this concept in the future, allowing researchers to accelerate further theoretical development in this area.